Spatial distribution of people with chronic diseases - Afrah Abbas Tashheel Al-Hassnawi, Rese.; Samee' Jallab Mansi Al-Sahlani, Prof. Dr. (lark, 2025)
The research aims to address the spatial dimensions of patients with chronic diseases in Dhi Qar Governorate, and the percentage of distribution of patients with these diseases. The research adopted the descriptive and analytical approach, and information was collected from health departments and hospitals in all administrative units in the governorate, related to chronic diseases. The research showed that the percentage of distribution of patients with high blood pressure in Shatrah District reached (50.11%), while Nasiriyah District came in second place with a percentage of (35.10%). While Al-Jabaish District came in first place with a percentage of (28.86%). As for asthma, Shatrah District came in first place with the highest percentage (43.76%) of the total number of patients with asthma, while Nasiriyah District came in second place with a percentage of patients (30.94%), while Souq Al-Shuyukh District came in last place with a percentage of patients (5.14%) of the total number of patients. As for patients with epilepsy, Al-Jabaish District came in first place with a percentage (28.86%) of the total number of patients with epilepsy in the study area, while Nasiriyah District came in second place with a percentage (23.54%) of the total number, while Al-Rifai District came in last place, with a percentage of patients with epilepsy (10.68%).